The Relationship Between Urban Planning and the Growth of Informal Settlements (A Field Study on a Sample of Residents of Informal Settlements in Ajdabiya City) - Warda Ahmed Mohamed Al-Sahli (Journal of Scientific and Human Dimensions, 2026)
The study aimed to examine the relationship between urban planning and the growth of informal settlements, using a mixed methodology (quantitative and qualitative) and descriptive-analytical approach. A questionnaire was used to collect data, and the study was applied to four informal settlements in the city of Ajdabiya using a snowball sample totaling 80 respondents. The study found that the reality of urban planning in the city does not take into account the equitable distribution of services (education, health, markets, transport, electricity, etc.) among its districts, and the efficiency of urban planning in the city is very weak because current urban plans do not include a fair distribution of residential and service areas and do not meet the future needs of the population. One of the main reasons for the growth of informal settlements is the low prices of land and properties in these areas, which contributed to their expansion and spread. There is also a very severe weakness in community participation in urban planning, as residents do not participate in urban decision-making and their opinions are not considered in the stages of preparing urban plans.